Mitigating the negative impact of the stray flux on the current transformers using flux equalizing windings. Issue 1 (31st December 2016) - Givi, Hadi; Shokrollahi Moghani, Javad; Samet, Haidar
Abstract: The accuracy of the current transformers (CTs) supplying the generator differential relay is essential in power plant stations. One important factor which decreases the CT accuracy is the stray flux originated from the adjacent phases. During external fault conditions, the currents of adjacent phases contain a considerable decaying DC component. Thus, corresponding fluxes also contain a decaying DC component which cannot be counteracted by bus bar enclosure and generator shell, completely. Hence, the CT output signal deviates from the correct waveform which may lead to undesirable operation of the differential relay supplied by the CT. In fact, there is no internal fault in the generator but the differential relay trips the breaker due to negative impact of stray flux on CT accuracy. In this paper, a real power plant bus bar is modeled using three-dimensional (3D) finite element method. Then, the effect of the stray flux on the accuracy of the CTs is studied. Finally, flux equalizing windings are considered on the CT's secondary winding. According to finite element simulation results, the negative impact of the stray flux on the CT accuracy is decreased considerably by the flux equalizing windings.